1989
DOI: 10.1177/089198878900200210
|View full text |Cite
|
Sign up to set email alerts
|

Head CT in New Geriatric Psychiatry Patients: A Prospective Study

Abstract: Computed tomography of the head (HCT) was studied prospectively in 42 new geriatric psychiatry patients. Scans were obtained in 88% of the sample. Subjects underwent a complete evaluation by a geriatric psychiatrist who was blind to the HCT results. The HCT was abnormal in 32 (86%) of the 37 patients who had a scan. The most frequent finding was atrophic changes, which were discovered in ten (27%) of the 37 patients. Subcortical vascular disease was found in 14 patients (38%). Mixed pictures with both vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The indications for referral for CT brain were based on the clinical judgement of the psychiatrist and the results showed that 64% showed some abnormality. In a prospective study by Chandler et al, 26 of the 42 new geriatric psychiatry patients included, 37 underwent CT scanning, of which 86% were abnormal. The authors suggest that the high yield was most likely because these were geriatric patients and the main abnormal finding was that of atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for referral for CT brain were based on the clinical judgement of the psychiatrist and the results showed that 64% showed some abnormality. In a prospective study by Chandler et al, 26 of the 42 new geriatric psychiatry patients included, 37 underwent CT scanning, of which 86% were abnormal. The authors suggest that the high yield was most likely because these were geriatric patients and the main abnormal finding was that of atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…86% of 37 patients 8 and 57% of 323 patients. 9 In contrast, Agzarian et al 10 reported that 95% of 397 patients at an acute tertiary service were within normal limits and McClellan et al…”
Section: Discussionmentioning
confidence: 99%
“…Daran hat sich bis heute nichts geändert, die Frage erhält sogar angesichts des zunehmenden Kostendrucks im Gesundheitswesen erhöhte Relevanz. Es zeigte sich jedoch, dass sowohl pathologische klinisch-neurologische Befunde als auch pathologische Befunde in testpsychologischen Untersuchungen und Elektroencephalogramm (EEG) zwar mit einer erhöhten Wahrscheinlichkeit pathologischer Befunde in der Bildgebung assoziiert, aber nicht ausreichend sensitiv und spezifisch sind, um sie zur Basis einer eindeutigen Indikationsstellung zu machen [4,7,8]. In den aktuell verfügbaren Behandlungsleitlinien werden daraus offensichtlich unterschiedliche Schlussfolgerungen gezogen: Wäh-rend die Leitlinien der Deutschen Gesellschaft für Psychiatrie, Psychotherapie und Nervenheilkunde (DGPPN) eine Bildgebung tendenziell empfehlen und bei manchen Störungsgruppen zumindest bei Erstaufnahme obligatorisch vorschreiben, verzichten die britischen, US-amerikanischen und australischen Leitlinien auf eine derartige Empfehlung [9 -18] Die gefundenen Ergebnisse aus der Routineversorgung lassen sich in Einklang mit der Studienlage bringen.…”
Section: Zusammenfassungunclassified